Rethinking on growth mechanism of Indian sugar industry. Issue 3 (8th July 2019) - Sheetal,; Kumar, Rajiv
Abstract : Purpose: The purpose of this paper is to revisit the growth mechanism of Indian sugar industry by deploying quantitative and qualitative metaphors. Design/methodology/approach: The research paper has been composed through comprehensive primary research survey using a structured questionnaire, and qualitative discussion following semi- structured interviews with industry professionals on emerging issues across the whole value chain of sugar industry. Respondents regarding primary survey were selected using the purposive sampling, and this collected quantitative information has been verified on the lenses of multiple stream modelling (MSM). Findings: To support the data analysis, MSM – a policy-making framework has been developed which found that government being a central construct exerts a profound presence across whole value chain; in suppliers' mechanism, marketing of sugar and sugar mills' infrastructural expansions. Nationwide uniformity in sugar policy instead of states' monopolistic policies, rational and mutual benefits-based decisions collectively by the government, mills management and sugarcane growers, and diversification in production processes are enumerated as the proposed solutions against the chronical industry problems. Practical implications: This study enriches extant Asian sugar industry literature. For policymakers, the proposed results should be of help in identifying specific policies to support the competitiveness of local systems and individual manufacturing companies in the Indian sugar industry suggesting that the development of growth mechanisms can contribute simultaneously to improve the financial, market and operational performance of both individual firms and supply chains. Originality/value: Cyclicality in production, rising sugarcane farmers' problems and resulting severe financial distress of mills are some of the topical issues of Indian sugar industry, and the study has explored these issues factually, quantitatively and qualitatively in proximity of industry professionals and described in this depository with the help of document analysis.